2006
DOI: 10.1590/s0066-782x2006001900009
|View full text |Cite
|
Sign up to set email alerts
|

Análise de séries temporais da mortalidade por doenças isquêmicas do coração e cerebrovasculares, nas cinco regiões do Brasil, no período de 1981 a 2001

Abstract: The risk of death due to cerebrovascular and ischemic heart diseases declined in the Southwest and South, which are the more developed regions of Brazil, whereas the risk increased in the less developed ones, mainly in the Northeast region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 8 publications
2
24
0
11
Order By: Relevance
“…Although stroke deaths have declined in the last decades 2,3 , recent mortality data also reveal cerebrovascular disease as the third cause of premature death after coronary heart disease and homicides 4 . However, the decrease in stroke mortality is not equally distributed across the country and it occurs mainly on the poorest areas of the country and among Blacks 5,6,7 .…”
mentioning
confidence: 99%
“…Although stroke deaths have declined in the last decades 2,3 , recent mortality data also reveal cerebrovascular disease as the third cause of premature death after coronary heart disease and homicides 4 . However, the decrease in stroke mortality is not equally distributed across the country and it occurs mainly on the poorest areas of the country and among Blacks 5,6,7 .…”
mentioning
confidence: 99%
“…Ressalta-se aqui uma redução de mortalidade menor no gênero masculino para as DIC (21,9%). Os resultados encontrados nesse estudo permitiram identificar que em cada triênio a magnitude dos coeficientes por DIC foi maior para o gênero masculino, aumentando com o avançar da idade em ambos os sexos para o estado, sendo esses achados corroborados por diversos autores que avaliaram as tendências de mortalidade em outros estados e municípios do Brasil [15][16][17][18] . Verificou-se no presente trabalho que a mortalidade por DIC aumentou e, para a população masculina, esse aumento já supera as DCBV no estado do Paraná.…”
Section: Discussionunclassified
“…In Latin America, stroke incidence rates adjusted for age vary between 35 and 183 per 100,000 6 , and, in Brazil, vary between 137 and 168 per 100,000 inhabitants [7][8][9] . In two recent studies of stroke-related mortality, a steady drop in mortality rates were observed in the last two decades 10,11 . Although the reasons for this drop are unknown, classically mortality rates are directly related to changes in incidence or lethality rates 11 .…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
“…In two recent studies of stroke-related mortality, a steady drop in mortality rates were observed in the last two decades 10,11 . Although the reasons for this drop are unknown, classically mortality rates are directly related to changes in incidence or lethality rates 11 . Incidence rates are influenced by socio-economical conditions and quality of primary prevention, while lethality is dependent on disease severity of the sample and quality of hospital care 11 .…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation